Implementing a Holistic Islamic Religious Education Curriculum Based on Multicultural Values - Anggraini, Miranti; Nadlir, Nadlir; Made, Enisa (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
This study examines the integration of a holistic approach in the development of an Islamic Religious Education (PAI) curriculum that incorporates Islamic multicultural values. Utilizing a qualitative, literature-based methodology, the research analyzes key educational frameworks and proposes a comprehensive curriculum that integrates spiritual, intellectual, social, and practical dimensions. The findings highlight the necessity for a PAI curriculum that balances cognitive, affective, and psychomotor aspects, while promoting inclusive, contextual, and student-centered learning. The core of the proposed curriculum is grounded in Islamic multicultural values, emphasizing tolerance, respect for diversity, and the promotion of social harmony. Key implementation strategies include the formulation of transformative learning objectives, the adoption of active-reflective teaching methods, and the incorporation of character-based assessments. However, challenges such as limited resources, a lack of teacher preparedness, and insufficient parental involvement are identified as barriers to successful implementation. The study concludes that fostering collaboration among educational stakeholders and enhancing teacher competencies are critical steps toward realizing a holistic PAI curriculum that reflects the values of Islamic multiculturalism, compassion, and social transformation